International Experience with Private Sector Participation in Power Grids : Turkey Case Study - World Bank Group (World Bank, Washington, DC, 2016)
Development of transmission and distribution (TD) infrastructure is crucial for the power systems. Regardless of the market models and the ownership structure, they have to be adequate for the continuity of the energy flow, the reliability of the power system and the quality of the energy supply. They have to be developed in parallel with the generation expansion in order to cope with the energy demand and to provide a sustainable service to the users and consumers. In this study, PSP practices of Turkey in TD have been investigated. In this respect; a general overview and historical background has been given in section two. The structural and regulatory aspects of PSP models in TD in the past and also after the reform have been explained in section three. It should be noted that, the PSP models used before the electricity market reform are also introduced in order to give information about different models. However, emphasis is given to the implementation of the recent PSP models. Results of implementation and problems are explained in sections four, five and six. Finally, conclusions, lessons learned and recommendations are discussed in section seven.